2002
DOI: 10.1016/s0301-0546(02)79095-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein profile in long term theophylline administration in children with asthma

Abstract: Atherosclerosis in childhood has a slowly progressive course and its clinical features usually become prominent in middle ages. Hypercholesterolemia is one of the major risk factors for the development of atherosclerosis. A clear correlation exists between hypercholesterolemia in childhood and atherosclerotic lesions extending into adulthood.In this study, we evaluated the effect of slow release theophylline (SRT) treatment on plasma lipid profile and assessed the risk for atherosclerotic coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The mechanism of effect was not clear. In another study, in children with asthma, the effect of slow release theophylline on lipid profile has also been reported and it was suggested that the lipid profile changes with extended use of these drugs and that this might cause an increased risk in atherosclerotic coronary heart disease 28 . In another study, HDL level was found to be significantly high in…”
Section: Discussionmentioning
confidence: 93%
“…The mechanism of effect was not clear. In another study, in children with asthma, the effect of slow release theophylline on lipid profile has also been reported and it was suggested that the lipid profile changes with extended use of these drugs and that this might cause an increased risk in atherosclerotic coronary heart disease 28 . In another study, HDL level was found to be significantly high in…”
Section: Discussionmentioning
confidence: 93%